Prevention Service System Transformation Using Communities That Care - Brown, Eric C. (2011)
This study examines prevention system transformation as part of a community-randomized controlled trial of Communities That Care (CTC). Using data from surveys of community leaders, we examine differences between CTC and control communities 4.5 years after CTC implementation. Significantly higher levels of adopting a science-based approach to prevention observed in CTC communities compared to controls in 2004 were maintained in 2007. Leaders in CTC communities expressed a willingness to contribute significantly more funds to prevention than did leaders in control communities in 2007. Significant differences in levels of community collaboration observed in 2004 were not maintained in 2007. Leaders in CTC communities with high poverty rates and large minority student populations reported higher levels of community norms against drug use and greater use of the social development strategy, respectively, than did leaders in control communities with similar characteristics.